Colonialismo en Península Valdés: entre los proyectos defensivos y las tentativas comerciales (Patagonia norte, fines del siglo XVIII). - Bianchi Villelli, Marcia (Memoria Americana)
At the Viceroyalty of the Rio de la Plata southern border, target of the colonization plan of the eastern Patagonian coast in late 18th century, three coastal forts were settled. This paper broadens the questions about one of them, Fuerte San José (Valdés Peninsula, Chubut Province, Argentina). Beyond the defensive plan seeking to reaffirm the Spanish presence in the region, we highlight the presence of the fort as shelter in a natural port and also as support for the exploitation of marine resources and salt, both available in the area Based in historical documents found in several archives, we have studied the first twelve years of operation in the Fort. As a result, the relationship between colonial planning coming from administrative centers and everyday development, attending to the actual incidence of foreign presence, interethnic relations, productive enterprises and colonial trade is been discussed.